Mannose Binding Lectin Mediated Complement Pathway in Multiple Sclerosis - Kwok, Janet Y. (2011)
Role of mannose binding lectin (MBL) complement activation pathway, an arm of innate immunity in multiple sclerosis (MS) was evaluated by analyzing the expression of MBL, MBL-associated serine protease -2 (MASP-2), and functional MBL/MASP-2 mediated C4 cleavage (fMBL) in 87 plasma and cerebrospinal fluid (CSF) samples from MS patients and non-MS controls. Median fMBL and MASP-2 plasma levels were higher in MS vs. non-MS cases. These associations remained in an analysis of subtypes of MS disease. These findings suggest a potential activation of MBL complement pathway in MS that may possibly alter the risk or progression of MS disease.